The training complex for learning Russian as a foreign language (RFL) "V dobryj put’!" and RFL computer-based training system - Romanov, Yu. A.; Romanov, A. Yu. (Национальный исследовательский университет "Высшая школа экономики", 2015)
A description of the nationally oriented training complex for learning Russian as a foreign language "V Dobryi Put’!" for German speakers which includes a textbook, an audio-supplement, a video-film and a test system is given. The computer-based training system, designed for this complex ensures effective teaching foreign students Russian phonetics, vocabulary, grammar, speech etiquette, and also facilitates the formation of the necessary communication skills.

Приводится описание национально-ориентированного учебного комплекса по РКИ для немецкоговорящих "В добрый путь!", который включает учебник, аудиоприложение, видеофильм и систему тестов. Разработанный для данного комплекса компьютерный тренажер обеспечивает эффективное обучение иностранных учащихся русской фонетике, лексике, грамматике, речевому этикету, а также облегчает формирование необходимых коммуникативных навыков.
Учебный комплекс для изучения русского языка как иностранного (РКИ) "В добрый путь!" и компьютерный тренажер по РКИ
Keywords: methods of learning a second language; Russian as a foreign language; RFL computer-based training system; educational process; методика обучения второму языку; учебный процесс; речевой этикет; иностранные студенты